A taxonomic revision of the continental African material previously included in Diospyros ferrea (Ebenaceae) - Edgard Mestre Serra; Carmen Puglisi; Alexander G. Linan; Nattanon Meeprom; Hasina N. Rakouth; Heidi H. Schmidt; Porter P. Lowry II (Plant Ecology and Evolution)
Background and aims – As currently circumscribed, Diospyros ferrea represents one of the most geographically widespread species in the genus and had previously been described as an ochlospecies because of its particularly challenging morphological complexity. Recent studies have shown that it likely contains multiple species that differ from populations in SW India and Sri Lanka corresponding to the type, which was collected on the Malabar coast in India. Here we present the second in a series of papers that aim to revise the taxonomy of D. ferrea, treating material from Africa. Material and methods – This study was based on measurements and observations of herbarium specimens from K, MO, and P as well as scanned images from BM, BR, C, COI, EA, FHO, LISC, US, and WAG. Species were delimited based on a combination of fruit and leaf characters, in conjunction with eco-geographic distribution. Specimen records were georeferenced, mapped, and used to conduct risk of extinction assessments based on the IUCN Red List criteria. Key results – Five well-delimited and geographically coherent species are recognized among the African material previously ascribed to Diospyros ferrea, including three described as new (D. angolensis, D. moutsambotei, and D. suaheliensis) and two for which new combinations are made (D. guineensis and D. smeathmannii). We provide a diagnostic key along with detailed morphological descriptions and photos illustrating the principal characters that distinguish the five species. Preliminary risk of extinction assessments indicate that only one of them is Least Concern, whereas three are Vulnerable, and one is Endangered. Conclusion – This revision demonstrates that taxonomically challenging ochlospecies can be resolved by careful analysis of morphological characters and geographic distribution, provided adequate material is available. Studies to clarify the nature, evolutionary history, and taxonomic status of other ochlospecies recognized by Frank White (viz. D. natalensis and D. mespiliformis) should be undertaken, but may also require additional phylogenetic and/or phylogeographic data.